Trend and Characteristics of 2, 636 Maxillofacial Fracture Cases over 32 Years in Suburban City of Japan. Issue 4 (December 2015) - Yamamoto, Kazuhiko; Matsusue, Yumiko; Horita, Satoshi; Murakami, Kazuhiro; Sugiura, Tsutomu; Kirita, Tadaaki
Trend and characteristics of maxillofacial fractures in 2, 636 patients over 32 years were analyzed retrospectively. Patients comprised 1, 764 males and 872 females with ages ranging from 0 to 99 years. Patients younger than 30 years consisted of 60% maxillofacial fractures in the early period but decreased to 40% in the late period. In contrast, patients older than 60 years gradually increased to 30%. In terms of cause, traffic accidents consisted of more than 50%, predominantly motorcycle accidents, but gradually decreased to 40%. In contrast, falls markedly increased from less than 10 to 30%. Fractures occurred in the midface in 938 patients, in the mandible in 1, 490, and in both in 208. In the midface, zygoma fractures consisted of 50% throughout the period. In the mandible, condyle fractures were observed in 40%, followed by fractures of the symphysis and angle. The ratio of condylar fractures slightly increased. Open reduction and internal fixation (ORIF) were performed in 782 patients, followed by observation in 716, maxillomandibular fixation (MMF) in 605, intramaxillary splinting (IMS) in 294, transcutaneous reduction (TCR) in 126, and others in 113. MMF markedly decreased from more than 30 to less than 5% and observation increased from 20 to 40%.